2021
DOI: 10.1038/s41467-021-21241-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IL-21 to tumor-reactive T cells enhances memory T cell responses and anti-PD-1 antibody therapy

Abstract: T cell rejuvenation by PD-1/PD-L1 blockade, despite emerging as a highly promising therapy for advanced cancers, is only beneficial for a minority of treated patients. There is evidence that a lack of efficient T cell activation may be responsible for the failure. Here, we demonstrate that IL-21 can be targeted to tumor-reactive T cells by fusion of IL-21 to anti-PD-1 antibody. To our surprise, the fusion protein PD-1Ab21 promotes the generation of memory stem T cells (TSCM) with enhanced cell proliferation. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…37 The generation of T SCM -like T cells in the presence of IL-21 has been described before. 38,39 As opposed to the results of Cieri et al, Chen and colleagues, who compared differentiation of T N to T SCM in the presence of IL-2, IL-7, IL-15 or IL-21 after aCD3/CD28 activation, showed that IL-21 has the highest potential to induce T SCM , 40 which is in line with our observations. Discrepancies in T SCM phenotype indicate differences between T SCM -like cells generated in vitro from HSPC in OP9-DL1 co-cultures (and subsequent agonist selection with the cognate peptide in the presence of cytokine(s), as compared to T SCM -like cells as generated in vitro starting from T N by Cieri et al and Chen et al (by activating T N with aCD3/aCD28 in the presence of cytokine(s)), and T SCM cells as isolated directly from healthy donors by Gattinoni et al 14,15,40 In their report, Vizcardo et al state that CD8 + SP T cells generated in OP9-DL1 co-cultures are 'abnormal', with high expression of NK cell markers, indicating innate-like features, and upregulation of PTCRA, RAG1, RAG2 and RORC, indicating an immature phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…37 The generation of T SCM -like T cells in the presence of IL-21 has been described before. 38,39 As opposed to the results of Cieri et al, Chen and colleagues, who compared differentiation of T N to T SCM in the presence of IL-2, IL-7, IL-15 or IL-21 after aCD3/CD28 activation, showed that IL-21 has the highest potential to induce T SCM , 40 which is in line with our observations. Discrepancies in T SCM phenotype indicate differences between T SCM -like cells generated in vitro from HSPC in OP9-DL1 co-cultures (and subsequent agonist selection with the cognate peptide in the presence of cytokine(s), as compared to T SCM -like cells as generated in vitro starting from T N by Cieri et al and Chen et al (by activating T N with aCD3/aCD28 in the presence of cytokine(s)), and T SCM cells as isolated directly from healthy donors by Gattinoni et al 14,15,40 In their report, Vizcardo et al state that CD8 + SP T cells generated in OP9-DL1 co-cultures are 'abnormal', with high expression of NK cell markers, indicating innate-like features, and upregulation of PTCRA, RAG1, RAG2 and RORC, indicating an immature phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…According to the authors, in vivo treatment with IL-21 leads to complete regression of FC-muMCL1 tumor in syngeneic mice through NK and T cell dependent mechanisms. Similar studies were also conducted by Li et al [29], who showed that IL-21 may affect T cells, which are involved in the anti-tumor response, by fusing with an anti-PD-1 antibody. Wang et al [30] assessed the role of interleukin 21 and its receptor in proliferation, migration, and invasion of breast cancer cells.…”
Section: Discussionsupporting
confidence: 77%
“…The combined use of IL-7 and IL-15 can preserve the T SCM phenotype and enhance the effectiveness of CAR-T cells (11,29,(58)(59)(60)(61). IL-21 was critical for the long-term maintenance and functionality of (67). At present, a large number of experiments have confirmed that these cytokines can promote the production of T SCM and have potential antitumor effects.…”
Section: Development Of T Scm Cells Manipulation To Produce T Scm Cells In (Ex) Vivomentioning
confidence: 99%